2009
DOI: 10.1016/j.abb.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of product release and metal ions in a metallonuclease

Abstract: Most nucleases rely on divalent cations as cofactors to catalyze the hydrolysis of nucleic acid phosphodiester bonds. Here both equilibrium and kinetic experiments are used to test recently proposed models regarding the metal ion dependence of product release and the degree of cooperativity between metal ions bound in the active sites of the homodimeric PvuII endonuclease. Equilibrium fluorescence anisotropy studies indicate that product binding is dramatically weakened in the presence of metal ions. Pre stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…Recently published single-turnover DNA cleavage data for PvuII as a function of Mg 2+ concentration indicate that for the PvuII system, catalysis involving one Mg 2+ per active site can indeed occur, but that a more efficient twometal-ion mechanism can be operative under higher Mg 2+ concentrations. 75 It was shown in the same study that one Ca 2+ or Mg 2+ per active site stimulates substrate binding similarly, but that a second Ca 2+ dramatically increases DNA binding affinity, while there is only a modest increase for Mg 2+ (see also Bellamy et al 76 ). For the PvuII system, it was concluded that the "more efficient two-metal-ion mechanism can be operative under saturating metal ion (in vitro) conditions".…”
Section: Resultsmentioning
confidence: 89%
“…Recently published single-turnover DNA cleavage data for PvuII as a function of Mg 2+ concentration indicate that for the PvuII system, catalysis involving one Mg 2+ per active site can indeed occur, but that a more efficient twometal-ion mechanism can be operative under higher Mg 2+ concentrations. 75 It was shown in the same study that one Ca 2+ or Mg 2+ per active site stimulates substrate binding similarly, but that a second Ca 2+ dramatically increases DNA binding affinity, while there is only a modest increase for Mg 2+ (see also Bellamy et al 76 ). For the PvuII system, it was concluded that the "more efficient two-metal-ion mechanism can be operative under saturating metal ion (in vitro) conditions".…”
Section: Resultsmentioning
confidence: 89%
“…It is very difficult to clearly interpret these data: While k cat is supposed to represent the chemical step, in reality its value also reflects the rate-limiting step. In the case of many enzymes including metallonucleases, this step is product release [45]. The composition of K m is also complex, comprised of a ratio of rate constants for enzyme-substrate complex formation and breakdown.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling the nucleic acid using the more appropriate nonlinear form of the Poisson-Boltzmann equation [56, 57] is beyond the scope of this study. However, we have published kinetic evidence to support a mechanism in which the enzyme binds metal ion(s) before substrate [45]. In this scenario, the nucleophile can form in the absence of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In addition, our extrapolated value of the overall catalytic rate, or “turnover rate constant”, k, for PvuII (k~1 sec −1 ) is comparable to previously reported values from ensemble measurements under the same buffer conditions (k~0.3 sec −1 ). 3739 …”
mentioning
confidence: 99%